The right to petition and its theoretical aspects. (Journal of actual problems of jurisprudence, 2016)
This article reveals the theory of civil norms – procedural law and their practical application governing action proceedings. Also made an analysis of the order of action proceedings and called attention to its enforcement.
Keywords: Constitution; claim; citizens; parties; court; judge; court proceedings; arguments; the prosecutor